'Working with humanitarians is a nightmare': Dynamics surrounding locally led peacebuilding in Somalia - Dustin Barter (ODI, 2024)
Somalia stands at a critical juncture with notable progress in stabilisation, better governance, billions in debt relief, joining the EAC, liberating territories from al-Shabab, and lifting the arms embargo. Yet, challenges still remain. The analysis reveals that the current aid system, dominated by international actors, creates a political economy that hinders locally-led peacebuilding. The volatility and scale of humanitarian aid have led to vested interests and disrupted long-term local civil society efforts. Despite these challenges, there are unique opportunities for international actors to support peacebuilding by increasing trust with Somali peace actors and adopting informed risk tolerance. Significant examples of successful locally-led actions include the Road to Sustainable Peace (RSP) and Nexus consortiums, demonstrating the importance of long-term, consistent, and flexible funding. The report also highlights the need for international aid actors to engage and collaborate more effectively with the Federal Government of Somalia (FGS) and other state authorities to ensure aid coherence and sustainability. This comprehensive report offers detailed findings and practical recommendations for international actors to enhance their support for peacebuilding in Somalia.
Keywords: 320; Peacebuilding; Somalia